The equation of the line passing through the points (x1, y1) and (x2, y2) is given by ( y - y1) = [( y2 - y1)/(x2 - x1)]( x - x1)

As the line passes through ( -1 , 3) and (3 , 1) we can substitute the values we have to get :

( y - 3) = [( 1 - 3)/(3 + 1)]( x + 1)

=> 4( y - 3) = -2( x + 1)

=> 2y - 6 = -x - 1

=> 2y = -x + 5

=> y = -x/2 + 5/2

=> f(x) = -x/2 + 5/2

**The required function is f(x)= -x/2 + 5/2**

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now